2021
DOI: 10.3390/jcm10163457
|View full text |Cite
|
Sign up to set email alerts
|

Role of miRNAs in Normal Endometrium and in Endometrial Disorders: Comprehensive Review

Abstract: The molecular responses to hormonal stimuli in the endometrium are modulated at the transcriptional and post-transcriptional stages. Any imbalance in cellular and molecular endometrial homeostasis may lead to gynecological disorders. MicroRNAs (miRNAs) are involved in a wide variety of physiological mechanisms and their expression patterns in the endometrium are currently attracting a lot of interest. miRNA regulation could be hormone dependent. Conversely, miRNAs could regulate the action of sexual hormones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“…In our own studies, we also showed significant differences in eutopic endometrium of women with endometriosis as compared to controls [ 104 , 105 ]. It is well documented that miRNA expression in the human endometrium is dependent on the menstrual cycle phase and is regulated by sex steroids [ 106 ]. A broad range of different miRNAs involved in the pathogenesis of endometriosis and ectopic pregnancy has been described and they are summarized in Figure 3 [ 35 , 106 , 107 , 108 ].…”
Section: The Role Of Micrornamentioning
confidence: 99%
See 1 more Smart Citation
“…In our own studies, we also showed significant differences in eutopic endometrium of women with endometriosis as compared to controls [ 104 , 105 ]. It is well documented that miRNA expression in the human endometrium is dependent on the menstrual cycle phase and is regulated by sex steroids [ 106 ]. A broad range of different miRNAs involved in the pathogenesis of endometriosis and ectopic pregnancy has been described and they are summarized in Figure 3 [ 35 , 106 , 107 , 108 ].…”
Section: The Role Of Micrornamentioning
confidence: 99%
“…It is well documented that miRNA expression in the human endometrium is dependent on the menstrual cycle phase and is regulated by sex steroids [ 106 ]. A broad range of different miRNAs involved in the pathogenesis of endometriosis and ectopic pregnancy has been described and they are summarized in Figure 3 [ 35 , 106 , 107 , 108 ]. In this part of the review, we focus on miRNAs that may constitute a link between these two diseases.…”
Section: The Role Of Micrornamentioning
confidence: 99%
“…Interestingly, the stability of several mRNAs is regulated by estrogens ( Ing, 2005 ). Several microRNAs (miRNA) control gene expression at the posttranscriptional level and can be induced or inhibited by estrogen ( Klinge, 2012 ; Kolanska et al, 2021 ). In addition, E2 canonical signaling pathways mainly mediated by nuclear estrogen receptors can perform as transcription factors to stabilize or destabilize mRNAs via miRNAs modifying gene expression ( Kim et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature data on the involvement of identified miRNA in embryo implantation and endometrial cancer are resumed in Table 2 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%